The food and environmental safety of Bt crops - Koch, Michael S.; Ward, Jason M.; Levine, Steven L.; Baum, James A.; Vicini, John L.; Hammond, Bruce G. (Frontiers in Plant Science, 2015)
Bt (Bacillus thuringiensis) microbial pesticides have a 50-year history of safe use in agriculture. Cry proteins are among the active insecticidal ingredients in these pesticides, and genes coding for Cry proteins have been introduced into agricultural crops using modern biotechnology. The Cry gene sequences are often modified to enable effective expression in planta and several Cry proteins have been modified to increase biological activity against the target pest(s). Additionally, the domains of different but structurally conserved Cry proteins can be combined to produce chimeric proteins with enhanced insecticidal properties. Environmental studies are performed and include invertebrates, mammals and avian species. Mammalian studies used to support the food and feed safety assessment are also used to support the wild mammal assessment. In addition to the NTO assessment, the environmental assessment includes a comparative assessment between the Bt crop and the appropriate conventional control that is genetically similar but lacks the introduced trait to address unintended effects. Specific phenotypic, agronomic, and ecological characteristics are measured in the Bt crop and the conventional control to evaluate whether the introduction of the insect resistance has resulted in any changes that might cause ecological harm in terms of altered weed characteristics, susceptibility to pests, or adverse environmental impact. Additionally, environmental interaction data are collected in field experiments for Bt crop to evaluate potential adverse effects. Further to the agronomic and phenotypic evaluation, potential movement of transgenes from a genetically modified crop plants into wild relatives is assessed for a new pest resistance gene in a new crop. This review summarizes the evidence for safety of crops containing Cry proteins for humans, livestock, and other non-target organisms.